2001
DOI: 10.1080/00420980120087153
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Neighbourhood Effects on Social Exclusion

Abstract: Interest in the influence of the neighbourhood on the life-chances of individuals has been increasing. However, methodological problems in identifying causal models of these influences suggest the need for caution in such inference. This paper uses data from the British Household Panel Study linked to local area characteristics to explore how far there is evidence that outcomes associated with social exclusion (non-monetary poverty measures, measures of labour market engagement, entry into jobs and flows in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
205
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(219 citation statements)
references
References 8 publications
3
205
0
11
Order By: Relevance
“…A major difficulty in neighbourhood research is identifying the relevant spatial scale of the neighbourhood and often the choice is driven by the availability of data and the detail of geo-references available. Both Buck (2001) and Bolster and colleagues (2007) found that local neighbourhoods provide more explanation than broader ones, showing how scale is crucial to the understanding of the effects identified. From this we may conclude that some studies might simply use the 'wrong' neighbourhoods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major difficulty in neighbourhood research is identifying the relevant spatial scale of the neighbourhood and often the choice is driven by the availability of data and the detail of geo-references available. Both Buck (2001) and Bolster and colleagues (2007) found that local neighbourhoods provide more explanation than broader ones, showing how scale is crucial to the understanding of the effects identified. From this we may conclude that some studies might simply use the 'wrong' neighbourhoods.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical evidence from studies investigating whether neighbourhood effects exist is mixed (Bolster et al, 2007). Durlauf (2004) reports that quasi-experimental studies, such as Gautreaux and the Moving to Opportunity program (Rosenbaum, 1995;Katz et al, 2001;Ludwig et al, 2001;Goering et al, 2002;Kling et al, 2004) find little impact on adults' outcomes while the bulk of non-experimental observational studies (see for examples using the British Household Panel Survey McColluch, 2001;Buck, 2001) do find effects. Durlauf (2004) identifies a range of conceptual and statistical problems that might explain why many observational studies find a negative effect of deprived neighbourhoods on individual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These negative consequences are mainly problematic for people who are not in a position to move away from disadvantageous neighbourhoods. Research has shown that deprivation in a neighbourhood can have many negative consequences, such as: the occurrence of teenage pregnancies (Anderson, 1999); low socioeconomic position (Galster, Metzger and Waite, 1999); school dropout (Overman, 2002); poor educational achievement; and retarded child development (Crane, 1991;Duncan, Brooks-Gunn and Klebanov, 1994); limited transfer from unemployment to work (Van der Klaauw and Ours, 2003); deviant behaviour (Friedrichs and Blasius, 2003); social exclusion (Buck, 2001); victimization (Sampson, Raudenbush and Earls, 1997); and poor access to the labour market (Ihlanfeldt and Sjoquist, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Siekiama atsakyti į klausimą, kaip lokaliose vietovėse susiformavę socialiniai ryšiai ir jų specifika gali paaiš-kinti tokius reiškinius kaip skurdo kultūra, nusikalstamumas, marginalizacija, nedarbas ir dalyvavimas darbo rinkoje, socialinių paslaugų tinklo infrastruktūra, erdvinė segregacija, politinis vietos gyventojų aktyvumas ir dalyvavimas įvairiose pilietinėse iniciatyvose ir pan. Vienas iš tokių tipiškų pavyzdžių yra Nicko Bucko socialinės deprivacijos priežasčių ir kaimynystės charakteristikų sąveikos tyrimas Didžiojoje Britanijoje (Buck 2001). Autorius formuluoja klausimą, ar specifinės vietos bendruomenių charakteristikos, tokios kaip vietos gyventojų šeimų socialinė sudėtis, išsilavinimas, amžius, nedarbo trukmė, profesinė patirtis gali lemti individualius pasirinkimus ir socialinio mobilumo galimybes deprivaciją patiriančiose kaimynys tėse.…”
Section: įVadasunclassified
“…Empirinių duomenų analizė rodo, kad kaimynystėse susiformavusi deprivacija lemia nematerialius skurdo rodiklius, kylančius dėl ribotų socialinio dalyvavimo ir vartojimo galimybių. Mažesnėse vietovėse ar bendruomenėse nematerialių išteklių trūku-mo efektas yra kur kas didesnis dėl stiprių socialinių ryšių tinklų, ribojančių mobilumą ir įvairių naudingų išteklių mainus (Buck 2001(Buck , 2272.…”
Section: įVadasunclassified